Kako povečati produktivnost pri obločnem varjenju? - Tušek, Janez (Kovine zlitine tehnologije, 1995)
Six different alternatives for rise in productivity in arc welding with consumable electrode are described, including welding with longer wire extension, welding with rotating material transfer and longer arc, welding with several welding heads, welding with multiple-wire eletrode, welding with metal powder additio and manual metal-arc welding with additional cooling of the electrode covering. In all the welding processes described, melting rate, i.e. quantity of filler material molten in time unit, is increased. Submerged arc welding, gas shielded arc welding and manual metal-arc welding with covered electrode are described. By applying the processes described, process productivity can be raised by 30% or even up to ten-times the value of the original melting rate.
Keywords: varjenje; obločno varjenje; talilni učinek; produktivnost